2016
DOI: 10.1159/000450603
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré Syndrome and Cerebral Hemorrhage: Two Cases and Literature Review

Abstract: Aims: The study aimed to investigate the potential relationships between Guillain-Barré syndrome (GBS) and cerebral hemorrhage. Methods: Two patients diagnosed with hemorrhagic stroke and GBS were reported. More specifically, the sequential occurrence and the corresponding mechanisms of these 2 diseases were analyzed. Results: Two patients with cerebral hemorrhagic stroke developed progressive flaccid quadriplegia and life-threatening dyspnea in acute stage. Combined with the cerebrospinal fluid and electromyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
(16 reference statements)
0
20
0
Order By: Relevance
“…[2] In recent years, weakness of extremities and weakened, or even loss of, tendon reflexes have been reported in some patients with traumatic brain injury, cerebral hemorrhage, spinal cord injury, brachial plexus injury, or pelvic fracture fixation. [3][4][5][6] In this article, we provide detailed clinical data of two patients who were diagnosed with GBS following brain hemorrhage or craniocerebral injury. The diagnosis of our 2 patients is based on the diagnostic criteria of GBS published in 2014, which was modified according to the criteria published in 1990.…”
Section: Introductionmentioning
confidence: 99%
“…[2] In recent years, weakness of extremities and weakened, or even loss of, tendon reflexes have been reported in some patients with traumatic brain injury, cerebral hemorrhage, spinal cord injury, brachial plexus injury, or pelvic fracture fixation. [3][4][5][6] In this article, we provide detailed clinical data of two patients who were diagnosed with GBS following brain hemorrhage or craniocerebral injury. The diagnosis of our 2 patients is based on the diagnostic criteria of GBS published in 2014, which was modified according to the criteria published in 1990.…”
Section: Introductionmentioning
confidence: 99%
“…Due to such autonomic dysfunction, hypertension, reversible cerebral vasoconstriction, and intracerebral hemorrhage are induced . On the other hand, as complications of immunoglobulin (IVIg), SAH and reversible cerebral vessel contraction syndrome were reported . In our patient, IVIg was intravenously administered before the onset of SAH.…”
Section: Discussionmentioning
confidence: 81%
“…In our case, the patient presented with GBS after spontaneous intraventricular hemorrhage. There are also a few cases that have reported that GBS can be caused by head trauma, neurosurgery, or other cerebral hemorrhagic injury ( Rivas et al, 2008 ; Yardimci et al, 2009 ; Tan et al, 2010 ; Song et al, 2012 ; Mantero et al, 2013 ; Zhang and Li, 2014 ; Wu et al, 2016 ; Li et al, 2017 ). Table 1 reviews the GBS cases that have developed after cerebral hemorrhagic injury (CHI).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are some GBS cases that have been described before CHI ( Table 2 ; Gande et al, 1999 ; Doss-Esper et al, 2005 ; Chang et al, 2014 ; Wei et al, 2015 ). Some of the possible mechanisms of GBS after CHI are the acute inflammation triggered by hemoglobin infiltration, disturbance of cellular humoral immunity after brain injury, and the stress state after hemorrhage ( Wu et al, 2016 ). However, the molecular mechanism leading to GBS is still unclear.…”
Section: Discussionmentioning
confidence: 99%